The Euro-crisis as a catalyst of the Europeanization of public spheres? A cross-temporal study of the Netherlands and Germany - Maurits Meijers (London School of Economics and Political Science (LSE), European Institute, 2013)
In this paper it is analysed whether the euro-crisis has induced a change in the degree of Europeanization of national public spheres. It is argued that 'mediatizing politics' on TV is a prerequisite for the accountability structures of liberal democracies. Examining the degree of Europeanization of public broadcaster news in Germany and the Netherlands in 2008 and 2011 this paper gauges the changes in terms of visibility of European issues and in terms of salience of items on European issues. Moreover it is analysed which news categories predominate, the tone of news items on European issues, and which explicit evaluations of European integration appear – and how these elements are affected by the euro-crisis. Finally, it is shown that although the Europeanization of public spheres increased as the euro-crisis developed, the EU was mostly portrayed negatively, focused predominantly on economic issues and political contestation was hardly visible.
Keywords: 330